Agronomic efficacy of Faidherbia albida (Del) A. Chev. leaf litter combined with organic manure on sorghum (Sorghum bicolor [L.] Moench) growth and yield. - CAMARA, Boubacar; DIATTA, André Amakobo; NDIAYE, Lemou; NDIAYE, Ibrahima; DIALLO, Thierno Amadou; Daouda, NGOM (Indian Journal of Agroforestry, 2025)
Sorghum is an essential plant in Africa, it is the second most widely grown cereal after millet. However, soil degradation such as deforestation, improper land management practices, and climate change, pose a threat to the optimal growth and yield of sorghum. Therefore, the utilization of organic amendments in agriculture is gaining prominence as a sustainable strategy to enhance crop yields while simultaneously promoting soil health. The aim of this study is to assess the effect of combining Faidherbia albida leaf litter and manure on sorghum growth and yield. A completely randomized design with five treatments and three replications was used. The treatments were the control (T0), Faidherbia leaf litter (T1) 5T/ha, the recommended rate of inorganic fertilizer (NPK (15:15:15) 150kg/ha and Urea 100kg/ha) (T2), farmers’ practice (manure) (T3) and the combination of F. albida litter and manure (T4). The results show that the organic amendments (T1, T3 and T4) gave the best performance in terms of sorghum growth and production parameters, with grain yields of 2.669 T/ha for T1, 2.477 T/ha for T3 and 2.327 T/ha for T4. However, the recommended rate of NPK had a positive influence on growth parameters but gave an average yield (1.134 T/ha) which was lower than the yield potential of sorghum (2 to 3 T/ha). The control treatment recorded the lowest seed yield with only 0.542 T/ha. The combination of litter and manure recorded the highest values for plant height, number of leaves, crown diameter and sorghum yield. Therefore, the combination of Faidherbia litter and manure could constitute a sustainable alternative to the use of chemical fertilizers for sorghum production.